Venture Capital Investment Model: The Aspect of Losing Soul "Due to the Current of the Times" - Dwiyatmi, Sri Harini; Novitasari, Selvie; Amitha, Exsa Nur Chika; Setyawan, Radiktya Ricky (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Venture capital was initially introduced in Indonesia as an alternative financing instrument oriented towards empowering small, medium, and startup businesses with growth potential. Through capital participation mechanisms, venture capital not only provides funds but also managerial support and access to business networks. Capital participation, which was initially driven by the spirit of economic equality, now tends to focus on profitability, valuation, and exit strategies. This shift has given rise to a phenomenon that can be termed "loss of soul," namely the fading of the social function and the goal of developing a people's economy, which is the philosophical background for the birth of venture capital. This article aims to legally examine the capital participation model in venture capital in Indonesia and analyze the shift in legal orientation that underlies it. This research uses normative legal research methods with statutory, conceptual, and comparative approaches. The analysis is carried out to assess the suitability between the prevailing legal norms and the ideals of economic empowerment that should be upheld. The results of the study show that venture capital regulations emphasize more on legal certainty for investors than protection for SMEs, resulting in an imbalance of interests. Therefore, legal reform and strengthening the role of the OJK are needed to ensure that the venture capital participation model retains the "soul" of empowerment, in line with the principle of social justice in national economic development